2003
DOI: 10.1016/s0735-1097(03)00577-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, morbidity, and quality of life after circumferential pulmonary vein ablation for atrial fibrillation

Abstract: Pulmonary vein ablation improves mortality, morbidity, and QoL as compared with medical therapy. Our findings pave the way for randomized trials to prospect a wider application of ablation therapy for AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
359
4
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 707 publications
(394 citation statements)
references
References 19 publications
20
359
4
11
Order By: Relevance
“…High heart failure rate in readmitted subjects in our study compared with Noseworthy et al13 is partly explained by the greater proportion of subjects aged ≥65 years in our study. Readmission rate because of stroke/TIA and bleeding noted in our study is similar to previously published studies 17, 20, 21, 22…”
Section: Discussionsupporting
confidence: 92%
“…High heart failure rate in readmitted subjects in our study compared with Noseworthy et al13 is partly explained by the greater proportion of subjects aged ≥65 years in our study. Readmission rate because of stroke/TIA and bleeding noted in our study is similar to previously published studies 17, 20, 21, 22…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have demonstrated that AF ablation improves QOL in a patient with symptomatic AF, including those with HF. 231,232 Many patients with AF have HF with reduced ejection fraction (EF). Multiple studies have examined the effect of ablation on EF.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…231,545 To date however, there are no RCTs verifying the hypothesis that ablation lowers the long-term incidence of stroke or TIA. Please refer to Section 7 for a more detailed discussion of the recommendations made by the writing group for long-term anticoagulation post-AF ablation.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…It is difficult to compare results across trials because of differences in the ablation techniques employed and the heterogeneity of patient populations enrolled (Table 1). 6,29 Catheter ablation appeared superior to AAD therapy in the multicenter Catheter Ablation Versus Antiarrhythmic Drugs for Atrial Fibrillation (A4) study. 7 The trial, limited to 4 centers, enrolled 112 patients with recurrent AF after treatment with ≥1 AAD.…”
Section: Catheter Ablation For Atrial Fibrillationmentioning
confidence: 99%
“…Insights derive from 1 relatively large observational study, 6 3 metaanalyses, 31 -33 and several smaller randomized trials. 29,34 -36 The observational study included 1171 consecutive patients treated by either complete PVI or medical therapy for AF.…”
Section: Comparison Of Ablation With Aadmentioning
confidence: 99%